1997
DOI: 10.1103/physrevb.56.8752
|View full text |Cite
|
Sign up to set email alerts
|

PrRu2Si2: A giant anisotropic induced magnet with a singlet crystal-field ground state

Abstract: The magnetic properties of PrRu 2 Si 2 have been investigated experimentally by specific heat, single-crystal magnetization, 141 Pr Mössbauer and muon spectroscopies, neutron powder diffraction, and inelastic neutron scattering, leading to the determination of its zero-field phase diagram and its crystal electric-field energy levels below 40 meV. PrRu 2 Si 2 undergoes a magnetic phase transition at T N Ӎ 16 K to an axial incommensurate sine-wave magnetic structure characterized by a wave vector ϭ ͑0.133, 0.13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
40
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 26 publications
(24 reference statements)
4
40
0
Order By: Relevance
“…21 A joint analysis of specific heat, magnetization, magnetic susceptibility, and inelastic neutron-scattering measurements suggests a singlet crystal-field ground state 12,13…”
Section: Discussionmentioning
confidence: 99%
“…21 A joint analysis of specific heat, magnetization, magnetic susceptibility, and inelastic neutron-scattering measurements suggests a singlet crystal-field ground state 12,13…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we have shown that the giant anisotropy field as large as 400 T observed in PrRu2Si2 [1,2] can be accounted for by crystal-field interactions. We are quite convinced in our crystal-field explanation for this giant magnetocrystalline anisotropy as it provides also a quite consistent description of other magnetic and electronic properties, like temperature dependence of the paramagnetic susceptibility and of the heat capacity.…”
mentioning
confidence: 89%
“…PrRu2Si2 exhibits a giant magnetocrystalline anisotropy about 400 T [1,2]. The aim of this contribution is to find the origin of this giant anisotropy, in the current literature as the source of the anisotropy three main factors are mostly discussed [1]: the anisotropic exchange, the hybridization, and the single-ion mechanism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Induced moment magnetic ordering in this compound would require very high internal exchange energy to achieve ordering. In some other Pr-based compounds like PrRu 2 Si 2 and PrNi 2 Si 2 , relatively smaller crystal field separations are (of 2.25 meV and 3.3 meV, respectively) [26,27]. In the present case of PrFe 2 Al 8 the knowledge of the first excited crystal field level first originated from a simulation of the Schottky specific heat, which predicts the first level at around 10 K. An estimation of the exchange constant is in general possible through the relation, θ p = JexJ(J+1) 3kB where θ p is the Curie-Weiss temperature and J ex is the exchange constant.…”
Section: Discussionmentioning
confidence: 99%